Influence of School Administrators’ Conflict Resolution Strategies on Teachers’ Job Satisfaction - John Christopher Ademola; Cyril Michael Ubala; Idris Mustapha Abdullahi (The Indonesian Institute of Science and Technology Research, 2023)
This paper was undertaken to determine the influence of school administrators’ conflict resolution strategies on teachers’ job satisfaction in GTCs of Kano State, Nigeria. A correlational research design was used in the study. 367 respondents comprising of 15 administrators and 352 Technical teachers in GTCs in Kano State form the population of the study. The sample size was 201 respondents selected using simple random sampling technique. Conflict Management Strategies Questionnaire (CMSQ), a structured questionnaire designed by the researchers, served as the data gathering tool. Three experts validated the instrument, and a reliability index of 0.82 was established using Cronbach Alpha. The questions in the study were answered using the mean statistic, and regression analysis with a 0.05 level of significance was used to test the null hypotheses. The findings revealed that: principals in GTCs in Kano State employed the following conflict-resolution techniques: negotiation, arbitration, effective communication, conversation, accommodation, harmonization, adjudication, and smoothing. Furthermore, to a moderate extent, the negotiation conflict management strategy influences teachers' job satisfaction. It was recommended that Government should provide more training for school administrators on the effective ways for conflict management resolution strategy to engender effective conflict resolutions in GTCs that will enhance teachers’ job satisfaction. Additionally, School administrators should encourage their staff to resolve their disputes through dialogue and be ready to abide by the outcome of the dialogue.